2014
DOI: 10.3747/co.21.1893
|View full text |Cite
|
Sign up to set email alerts
|

Protective Skin Care Behaviors in Cancer Survivors

Abstract: (1) Purpose: Research suggests that physicians neglect preventive care for cancer survivors. A survivor’s self-motivation with respect to preventive care is unknown. Using protective skin care as a proxy, our aims were to characterize preventive care in cancer survivors and to identify factors associated with appropriate prevention. (2) Methods: Using data from the 2009 U.S. Health Information National Trends Survey, we compared preventive skin care patterns in cancer survivors and non-cancer patients. Primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 27 publications
1
7
0
1
Order By: Relevance
“…Photoprotection should be counseled to all HCT recipients as it can reduce the risk of skin cancer. 2022 Physical examination is the primary method for skin cancer screening. Heightened awareness is warranted for patients who received myeloablative TBI, those who had HCT at ages < 18 years, those with prior or concurrent GVHD of any form and those who had HCT for hereditary disorders, such as Fanconi anemia.…”
Section: Methodsmentioning
confidence: 99%
“…Photoprotection should be counseled to all HCT recipients as it can reduce the risk of skin cancer. 2022 Physical examination is the primary method for skin cancer screening. Heightened awareness is warranted for patients who received myeloablative TBI, those who had HCT at ages < 18 years, those with prior or concurrent GVHD of any form and those who had HCT for hereditary disorders, such as Fanconi anemia.…”
Section: Methodsmentioning
confidence: 99%
“…The effects of (non‐skin) cancer diagnosis as an adult on sun exposure behaviours are unknown. Some research has shown that survivors of skin cancer and childhood cancers are more likely to exhibit behaviours that limit their sun exposure compared to control groups, and may modify their sun exposure habits in response to earlier (skin) cancer diagnosis, treatment and survival. The participants in the present study were at different stages of their cancer journey.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, while some patients may be capable and willing to engage in self-screening practices, others may feel overwhelmed and reluctant to do so, or may simply not be willing to engage in preventive activities (Lau et al, 2014).…”
Section: The Patient Viewmentioning
confidence: 99%